(untitled) (Terr@ Plural, 2020)
The digital models of landform representation allow several types of geomorphological analysis, such as assessing prone areas to the mass movement. Among the data set that applied to elaborate such models, LiDAR (Light Detection and Ranging) technology has stood out due to its capacity to represent in detail terrain specific characteristics. This work aimed to present a variety of studies based on LiDAR to evaluate slope instability and to describe an interpolation test of LiDAR raw data to generate a Digital Terrain Model considering different interpolation approaches, in an area affected by shallow landslides. The results show that the tool applied is efficient when combined Triangulation to Natural Neighbor methods.